2019
DOI: 10.1016/j.joule.2018.11.026
|View full text |Cite|
|
Sign up to set email alerts
|

Dion-Jacobson Phase 2D Layered Perovskites for Solar Cells with Ultrahigh Stability

Abstract: Dion-Jacobson (DJ) phase 2D layered perovskites are developed by removing the van der Waals gap between organic layers and inorganic slabs in Ruddlesden-Popper (RP) phase counterparts. The hydrogen bonding formed at both sides of diammonium cations with perovskite layers in the DJ phase 2D perovskite endows it with extremely high structural stability, compared with that at only one side in the RP phase one. The devices exhibit a PCE of 13.3% with unprecedented stability, even when subjected to very harsh testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
484
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 483 publications
(491 citation statements)
references
References 38 publications
6
484
0
1
Order By: Relevance
“…The large penetration depth broadens the distance between the NH 3 + and the nearest I (Supporting Information, Figure S4), and correspondingly weakens electronic interaction and the hydrogen bonding, leading to large Sn‐I‐Sn angles (Supporting Information, Table S2). It has been reported that the penetration depth influences the octahedral distortion, which expressed in their physical properties . The large Sn‐I‐Sn angles suggests small distortion with high crystal symmetry of (BEA)FA 2 Sn 3 I 10 , which shows an approaching band gap with respect to 3D FASnI 3 (details in the following discussion).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The large penetration depth broadens the distance between the NH 3 + and the nearest I (Supporting Information, Figure S4), and correspondingly weakens electronic interaction and the hydrogen bonding, leading to large Sn‐I‐Sn angles (Supporting Information, Table S2). It has been reported that the penetration depth influences the octahedral distortion, which expressed in their physical properties . The large Sn‐I‐Sn angles suggests small distortion with high crystal symmetry of (BEA)FA 2 Sn 3 I 10 , which shows an approaching band gap with respect to 3D FASnI 3 (details in the following discussion).…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, the perovskite layers in the (BEA)FA n −1 Sn n I 3 n +1 ( n >1) structure is slightly offset (Figure d) owing to the soft character of macromolecular ligand, which caused large penetration depth (defined by the distance between the primary NH 3 + and the plane of terminal iodides) of NH 3 + groups . The penetration depth of (BEA)FA n −1 Sn n I 3 n +1 ( n >1) is 0.923 Å (Supporting Information, Figure S3), which is much larger than the previous report on DJ structures . The large penetration depth broadens the distance between the NH 3 + and the nearest I (Supporting Information, Figure S4), and correspondingly weakens electronic interaction and the hydrogen bonding, leading to large Sn‐I‐Sn angles (Supporting Information, Table S2).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Later on, Ma et alreport a 13% efficiency using 1,3‐diaminopropane as spacer with methylammonium chloride (MACl), dimethyl sulfoxide (DMSO) as additive. After that, Ahmad et al reported a highly efficient 13.3% DJ phase PSCs with thousand hours ultrahigh stability using the same molecule. Zheng et al reported 16.38% efficiency DJ PSCs with MAAc molten salt as solvent; Li et al reported 14.86% efficiency for (BEA) 0.5 MA 3 Pb 3 I 10 DJ PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…For an ideal 3D perovskite structure, a t-value of 1 is desired and within the allowed range between 0.8 and 1, tilting of the BX 6 octahedra is noted , leading to a quasi-ideal perovskite structure. In addition, perovskites can dispose into layered phases constituting 2D BX 6 octahedra with interspersed cations forming the so-called Ruddlesden-Popper, [12] Aurivillius, [13] and Dion-Jacobson phases [14] (see Panel A, Figure 1). [4,5] This model determining geometry, shape, and size of crystal motifs is particularly applicable for fluorides and oxides because of their high electronegativities making the nature of their bonding increasingly ionic.…”
mentioning
confidence: 99%